HIV-1 gp120 and morphine induced oxidative stress: role in cell cycle regulation - Samikkannu, Thangavel; Ranjith, Deepa; Rao, Kurapati V. K.; Atluri, Venkata S. R.; Pimentel, Emely; El-Hage, Nazira; Nair, Madhavan P. N. (Frontiers in Microbiology, 2015)
HIV infection and illicit drugs are known to induce oxidative stress and linked with severity of viral replication, disease progression, impaired cell cycle regulation and neurodegeneration. Studies have shown that morphine accelerates HIV infection and disease progression mediated by Reactive oxygen species (ROS). Oxidative stress impact redox balance and ROS production affect cell cycle regulation. However, the role of morphine in HIV associated acceleration of oxidative stress and its link to cell cycle regulation and neurodegeneration has not been elucidated. The aim of present study is to elucidate the mechanism of oxidative stress induced glutathione synthases (GSS), super oxide dismutase (SOD), and glutathione peroxidase (GPx) impact cell cycle regulated protein cyclin-dependent kinase 1, cell division cycle 2 (CDK-1/CDC-2), cyclin B, and cell division cycle 25C (CDC-25C) influencing neuronal dysfunction by morphine co-morbidity with HIV-1 gp120. It was observed that redox imbalance inhibited the GSS, GPx and increased SOD which, subsequently inhibited CDK-1/CDC-2 whereas cyclin B and CDC-25C significantly up regulated in HIV-1 gp120 with morphine compared to either HIV-1 gp120 or morphine treated alone in human microglial cell line. These results suggest that HIV positive morphine users have increased levels of oxidative stress and effect of cell cycle machinery, which may cause the HIV infection and disease progression.